2008
DOI: 10.1007/s12206-008-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary application of the draft code case for alloy 617 for a high temperature component

Abstract: The ASME draft Code Case for Alloy 617 was developed in the late 1980s for the design of very-high-temperature gas cooled reactors. The draft Code Case was patterned after the ASME Code Section III Subsection NH and was intended to cover Ni-Cr-Co-Mo Alloy 617 to 982qC (1800qF). But the draft Code Case is still in an incomplete status, lacking necessary material properties and design data. In this study, a preliminary evaluation on the creep-fatigue damage for a high temperature hot duct pipe structure has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Therefore, a thorough knowledge of the elastoplastic behavior is necessary in the design and life evaluation of such components that operate in the high temperature condition. Although Alloy 617 has many superior properties, many researchers have reported that the number of cycles to failure varies widely at high temperatures [5][6][7][8][9]. However, they did not provide sufficient data on the Alloy 617 in the LCF regime over a range of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a thorough knowledge of the elastoplastic behavior is necessary in the design and life evaluation of such components that operate in the high temperature condition. Although Alloy 617 has many superior properties, many researchers have reported that the number of cycles to failure varies widely at high temperatures [5][6][7][8][9]. However, they did not provide sufficient data on the Alloy 617 in the LCF regime over a range of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary evaluation for a creep-fatigue damage according to the draft code case was carried out on a hot duct piping for the Alloy 617 material. Then the creep-fatigue damage equation for the Alloy 617 material according to the draft code case was calculated as [9] 18.8 82732…”
Section: Evaluation Of the Creep-fatigue Damage For The Hgdmentioning
confidence: 99%
“…An evaluation for creep-fatigue damage according to the ASME-NH was carried out for the hot duct piping for the Alloy 800H material. Thus the creep-fatigue damage equation for Alloy 800H according to the ASME-NH calculation was calculated as [9] Advanced Materials Research Vols. 33-37 42.4 396.9…”
Section: Evaluation Of the Creep-fatigue Damage For The Hgdmentioning
confidence: 99%
See 1 more Smart Citation